Environmental capacity and fluxes of land-sourced pollutants around the Leizhou Peninsula in the summer - Chen, Ying; Sun, Yan; Shi, Haiyi; Zhao, Hui; Gao, Hui; Pan, Gang; Tian, Kai (Frontiers in Marine Science, 2023)
Although the water environment has certain self-purification capability, the natural balance is disrupted, leading to water quality deterioration when the discharge load of wastewater exceeds a certain threshold. This problem implies the urgency of evaluating marine environmental capacity as a necessary parameter for marine sustainable development of marine ecosystems. Through principal component analysis (PCA), clustering, and other methods, we analyzed the average concentration and fluxes of land-sourced pollutants and determined the pollution level around the Leizhou Peninsula. Combined with the Delft3D hydrodynamic numerical model, tidal hydrodynamic forces and pollutants migration and diffusion were calculated. Based on in-situ measured data, the model was validated. The sharing rate method was used to calculate the marine environmental capacity in Zhanjiang Bay and analyzed their impact on seawater eutrophication. The results showed that: (1) The average concentrations of chemical oxygen demand (COD), ammonia nitrogen (NH4+), total nitrogen (TN), and total phosphorus (TP) around Leizhou Peninsula were 22.56 mg/L, 0.69 mg/L, 6.69 mg/L, and 0.69 mg/L, respectively. (2) Six areas (Area A-F) can be divided into, based on the discharge of land-sourced pollutants into the sea area. According to the results of PCA, clustering, and other methods, the average concentration and fluxes of land-sourced pollutants in Area B (i.e. Zhanjiang Bay) were very high. (3) The environmental capacity of Zhanjiang Bay was calculated through Delft3D numerical simulation, and it was found that the COD and TN environmental capacity of 6 sewage outlets exceeded the standard, while the TP environmental capacity of 3 sewage outlets exceeded the standard. (4) According to the statistical research result, most of the Zhanjiang Bay waters has been restricted by nitrogen for over a decade. Therefore, we speculate that although TN environmental capacity exceeds the standard, its impact on eutrophication in Zhanjiang Bay is still limited to a certain extent.